Efficient cross-coupling reaction of functionalized alkyl bromides with aryl halides by using electrochemical method - Abdul Jalil, Aishah; Kurono, Nobuhito; Takasugi, Shingo; Tokuda, Masao (2004)

(untitled)
Highly reactive zinc metal was readily prepared by electrolysis of a DMF solution containing naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. This reactive zinc (EGZn/Naph) was used for transformation of bromoalkanes into the corresponding organozinc bromides, which can not be achieved by the use of usual zinc metals. Reaction of the organozinc compounds thus prepared with various aryl iodides in the presence of 5 mol% of palladium catalyst gave the corresponding cross-coupling products in hick yields. Arylzinc iodides were also prepared by the use of EGZn/Naph and they were reacted with other aryl iodides to give the corresponding cross-coupled biaryl in good yields.